Genomic dissection of productivity, lodging, and morpho‐physiological traits in Eragrostis tef under contrasting water availabilities - Muluken Demelie Alemu; Shiran Ben‐Zeev; Timo Hellwig; Vered Barak; Gil Shoshani; Assaf Chen; Stephane Razzon; Ittai Herrmann; Alexandra Vorobyova; Sariel Hübner; Yehoshua Saranga (Plants, People, Planet)
Societal Impact Statement Underutilized species (also known as orphan crops) present opportunities to increase crop diversity and food security. Such crops lack modern genetic tools and knowledge to facilitate efficient modern breeding approaches. A wide collection of tef (Eragrostis tef (Zucc.) Trotter) genotypes was used to identify genomic regions associated with productivity, lodging, and morpho‐physiological traits under contrasting water availabilities. The obtained results are expected to enhance modern breeding and improve tef productivity under traditional and modern cropping systems, thus improving farmers' livelihood and food security. Summary Tef (E. tef (Zucc.) Trotter) is an allotetraploid (2n = 4x = 40) C4 cereal crop, endemic to Ethiopia and mainly cultivated in the Horn of Africa. Tef is characterized by high grain and feed nutritional qualities and resilience to abiotic and biotic stresses; thus, it holds great potential to sustain food and nutrition security in Africa and other parts of the world. The objective of this study was to identify genomic regions associated with responses to contrasting water regimes, as a basis for future improvement. A tef diversity panel was genotyped with 28,837 single nucleotide polymorphisms (SNPs) and phenotyped for productivity, lodging, and morpho‐physiological traits along two seasons (2020 and 2021) under well‐watered and water‐limited treatments. A genome‐wide association study was performed to identify genomic regions associated with key traits for tef breeding. A total of 107 SNPs were associated with one or more of the studied traits, resulting in 138 marker–trait associations (MTAs) detected under both water treatments. Of these, 22 SNPs were associated with more than one trait, showing either multiple trait (pleiotropic) or multiple environment associations or both. A particularly strong association was found between grain yield, lodging, and time to heading. These findings open new avenues to further research on the genetic basis and physiological mechanisms underlying major traits in tef, as well as to marker‐assisted breeding of drought‐resilient tef cultivars.